Strategie i taktyki rodzicielskie w zachowaniu języka odziedziczonego na obczyźnie, czyli o polskiej rodzinnej polityce językowej - Seretny, Anna; Lipińska, Ewa (Neofilolog, 2026)
Research in the field of heritage language maintenance and loss regards the family as the central driving force in child language acquisition and maintenance. The article focuses on the emerging field of family language policy and addresses one of its three components, namely family practices, bearing in mind that the stress-inducing factor of emigration may have a direct impact on them. A brief historical overview of the term, family language policy, is given, also for the Polish context. Illustrative examples of potential parental strategies and tactics follow, together with reflections based on data from surveys conducted by the research team of the Jagiellonian University. The text, by disclosing discrepancies between parents’ declarations and evidence from teenager users of heritage Polish, contributes to the discussion of language policies and maintenance of Polish as a heritage language.